The role of different urban amenities in attracting knowledge workers: Presenting the research design and first results - Jan Rouwendal; Jasper Dekkers; Jaap Boter (European Regional Science Association (ERSA), 2013)
Apart from housing quality and employment accessibility, knowledge workers are relatively strongly attracted by urban amenities such as the presence of shops, a variety of restaurants, recreational public spaces (e.g., parks), and by cultural facilities such as theaters, musea and cinemas. Since the knowledge-intensive and often specialised jobs these people qualify for are only available in a small number of larger metropolitan areas, they also tend to be more mobile (both within and across countries) than others and this makes it even more important to keep/make the urban area attractive for them. Human capital is a fundamental factor for every major urban agglomeration in modern-day society and economy. Urban amenities facilitate face-to-face contact both for pleasure and for productivity. Hence, the aim of this paper is to investigate the relationship between these amenities and the presence of highly-educated knowledge workers: do the amenities respond, through time, to the presence of knowledge workers or lack thereof, and to what extent? Increased insight in the relationship between amenities and knowledge workers can offer local policy makers better tools for planning strategies to attract more highly-educated people with high incomes to the urban area. We aim to do this analysis on a highly-detailed spatial scale-level (e.g. four-digit zip code areas or neighbourhoods) by linking lifestyle-data on level of education, income, et cetera about inhabitants (with a special focus on highly-educated knowledge workers) to detailed data about different types of urban and cultural amenities in the vicinity using distance-decay functions. We plan to first do a cross-section analysis to explore the relationships. To address causality issues, we will subsequently expand our analysis by including a time-dimension in our model. Both data sets are available on a detailed spatial scale and for a series of years.
Keywords: 330; highly educated workers; cultural amenities; globalisation